Effect of pemafibrate on fatty acid levels and liver enzymes in non‐alcoholic fatty liver disease patients with dyslipidemia: A single‐arm, pilot study. Issue 12 (1st October 2020) - Seko, Yuya; Yamaguchi, Kanji; Umemura, Atsushi; Yano, Kota; Takahashi, Aya; Okishio, Shinya; Kataoka, Seita; Okuda, Keiichiroh; Moriguchi, Michihisa; Okanoue, Takeshi; Itoh, Yoshito
Abstract : Aim: Dyslipidemia (DL) is commonly associated with non‐alcoholic fatty liver disease (NAFLD). Pemafibrate, a selective peroxisome proliferator activated receptor α modulator (SPPARMα), has been shown to improve liver function among patients with DL. The aim of this single‐arm prospective study is to evaluate the efficacy of pemafibrate in NAFLD patients with DL. Methods: Twenty NAFLD patients with DL who received pemafibrate (0.1 mg) twice a day for 12 weeks were prospectively enrolled in this study. The primary end‐point was change in serum alanine aminotransferase (ALT) levels from baseline to week 12. Results: Serum ALT levels decreased from 75.1 IU/L at baseline to 43.6 IU/L at week 12 ( P = 0.001). Significant improvements in triglyceride, high‐density lipoprotein cholesterol, total fatty acid, saturated fatty acid (SFA), and unsaturated fatty acid were also noted. The serum level of remnant‐like protein cholesterol, SFA, and polyunsaturated / saturated fatty acid ratio (PUFA / SFA ratio) at baseline were correlated with change in ALT level (r = −0.53, r = −0.57, and r = 0.46, respectively). Change in PUFA and change in PUFA / SFA ratio were negatively correlated with change in ALT level (r = −0.49 and r = −0.53). No hepatic or renal adverse events were reported. Conclusions: Selective peroxisome proliferator activated receptor α could be a promising novel agent for treatment of NAFLD patients with DL by regulating fatty acid composition. A further long‐term large‐scale trial is warranted to confirm the efficacy of SPPARMα on NAFLD with DL.